A longitudinal study of dispositional compassion in Syrian origin young adults resettling in the Netherlands. Issue 4 (July 2022) - Laceulle, Odilia M.; Stellar, Jennifer E.; Kinan, Alajak; Eva, Alisic; Zeina, Al Sawaf; Laurien, Meijer; Moopen, Neha; Trudy, Mooren; Ozoruç, Ilayda; Haza, Rahim; Taşfiliz, Duygu; Zonneveld, Renée; et al.
Background: Dispositional compassion is regarded as a facet of Agreeableness, an emotional driver of prosociality, and a primary marker of adjustment. We examined changes in dispositional compassion in Syrian young adults resettling in the Netherlands, as well as the role of migration-related and demographic variables in this change. Methods: We analyzed data from a 4-wave (T1-T4), 13-month longitudinal study ( N = 168; T1 Mage = 28.1 years, 70% male) using Latent Growth Curve Modelling (LGCM) in Mplus. Results: Bivariate correlations indicated moderate test-retest correlations across the four waves of dispositional compassion and several correlations with the migration-related and demographic variables. A LGCM indicated a high initial level and small linear decrease in compassion over the four waves. Except for a link between pre-migration adversity and the intercept, the migration-related and demographic variables were not related to either the intercept of the slope of dispositional compassion. Conclusion: Results suggest that high levels of dispositional compassion may be common for Syrian young adults with refugee backgrounds, but on average, slowly decreases over time. The cross-sectional associations between migration-related and demographic variables and dispositional compassion in the absence of a prospective one emphasize the importance of longitudinal research for understanding trajectories of adjustment.